Phosphorus and iron content in apples in different sales channels - Marko Petek; Matilda Povodnik; Tomislav Karažija; Mihaela Šatvar Vrbančić; Mile Markoski; Tomaš Lošak; Goran Fruk (University of Agronomic Sciences and Veterinary Medicine of Bucharest - Faculty of Horticulture Address: 59 Mărăşti Blvd, District 1, 011464, Bucharest, Romania E-mail: journal@horticultura-bucuresti.ro, Webpage: www.horticultura-bucuresti.ro, 2025)
Phosphorus and iron are essential elements that are necessary for various functions of plants, but also for humans. The apple, Malus × domestica Borkh., is one of the most consumed fruits in the world, also in Croatia. Since the mentioned elements influence the growth and development of the plant and also have certain health effects on humans, the presence of these elements in apples on the Zagreb market should be investigated. After collecting and sampling the apples, the phosphorus content was determined by spectrophotometry and the iron content by atomic absorption spectrometry. Apples from retail chains statistically have the highest average phosphorus content in dry matter (0.14 % P DW), while apples from organic products stores statistically have the highest phosphorus content in fresh weight (27.29 mg P/100 g fresh weight). As for iron, the statistically highest average content in both dry matter and fresh matter was found in apples from retail chains (15.99 mg Fe/kg DM and 0.261 mg Fe/100 g fresh weight). These results could be the consequences of conventional agriculture.
Keywords: fruit quality, Malus × domestica Borkh., market distribution, minerals, nutritional value